The impact of investment in knowledge-based capital on productivity: Firm-level evidence from Ireland - Mattia Di Ubaldo; Iulia Traistaru (The Economic and Social Research Institute (ESRI), 2017)
This paper examines the impact of investment in knowledge-based capital on firm productivity. The analysis is based on a dynamic econometric model estimated with micro-data from Ireland over the period 2006-2012. We use broad measures of investment in knowledge-based capital which include expenditures on R&D, and on non-R&D intangible assets such as computer software, copyrights, patents and licences, royalties and organisational capital. The results indicate that on average, over and above other factors, an increase in investment in knowledge-based capital of 10 per cent increases firm productivity by 2 per cent. The research results indicate that productivity gains linked to investment in KBC are larger for Irish-owned firms in comparison to foreign-owned firms. Further, the estimates indicate that firms' productivity is more responsive to investment in R&D than to investment in non-R&D intangible assets.
Keywords: F61; L22; O33; 330; Investment in intangible fixed assets; productivity; firm heterogeneity